2020
DOI: 10.1186/s13578-020-00466-4
|View full text |Cite
|
Sign up to set email alerts
|

MSC-based therapy in female pelvic floor disorders

Abstract: Mesenchymal stem cells (MSCs), also referred to as multipotent stromal cells or mesenchymal stromal cells, are present in multiple tissues and capable of differentiating into diverse cell lineages, holding a great promise in developing cell-based therapy for a wide range of conditions. Pelvic floor disorders (PFDs) is a common degenerative disease in women and may diminish a woman’s quality of life at any age. Since the treatments for this disease are limited by the high rates of recurrence and surgical compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…It uncovered more than 1000 clinical trials when we searched the keywords "mesenchymal stem cell" or "mesenchymal stromal cell" in the ClinicalTrials.gov database (http://www.clinicaltrials.gov/, accessed on June 2021). Despite the tremendous achievements made in MSCs therapy [3,[7][8][9][10][11], there are several limitations toward their clinical translation, such as invasive cell collection procedures, orchestrated engraftment steps, low posttransplantation cell viability, poor homing, and multiple doses to maintain the therapeutic effects [12][13][14][15]. Promisingly, accumulating experimental and clinical studies reveal that the powerful therapeutic agents of MSCs are mainly exerted by their paracrine effects, in particularly by exosomes [13,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It uncovered more than 1000 clinical trials when we searched the keywords "mesenchymal stem cell" or "mesenchymal stromal cell" in the ClinicalTrials.gov database (http://www.clinicaltrials.gov/, accessed on June 2021). Despite the tremendous achievements made in MSCs therapy [3,[7][8][9][10][11], there are several limitations toward their clinical translation, such as invasive cell collection procedures, orchestrated engraftment steps, low posttransplantation cell viability, poor homing, and multiple doses to maintain the therapeutic effects [12][13][14][15]. Promisingly, accumulating experimental and clinical studies reveal that the powerful therapeutic agents of MSCs are mainly exerted by their paracrine effects, in particularly by exosomes [13,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…six weeks after VD, showed that DMSC treatment increased the integrity of the muscle fibers of the EUS, in which little ECM infiltration and larger elastic fibers were found, compared with the extensive disruption of the muscle fibers found in the EUS of untreated animals. MSC isolated from muscle ( Cui et al, 2018 ; Bortolini et al, 2019 ), urine ( Wu et al, 2019 ), and adipose tissue ( Cui et al, 2018 ; Ni et al, 2018 ) have also been used experimentally in the VD animal model of SUI, showing that MSC induced morphological and histological regeneration and improved urinary function in rats through a paracrine process ( Sima and Chen, 2020 ). This paracrine effect could be stimulated, at least in part, by the hypoxic microenvironment generated by the VD.…”
Section: Discussionmentioning
confidence: 99%
“…There are many sources of MSC such as bone marrow, adipose tissue, or perinatal derivatives, among others ( Ledesma-Martinez et al, 2016 ; Torre and Flores, 2020 ; Gao et al, 2021 ; Krawczenko and Klimczak, 2022 ). MSC transplantation has been tested in preclinical SUI models and has been shown to be safe, feasible, and effective in repairing tissue deficiencies ( Sima and Chen, 2020 ; Maiborodin et al, 2022 ). MSC from different tissues have been tested in these preclinical models such as from bone marrow ( Janssen et al, 2019 ), adipose tissue ( Cui et al, 2018 ; Ni et al, 2018 ), dental pulp ( Zordani et al, 2019 ), urine ( Wu et al, 2019 ), and muscle ( Bilhar et al, 2018 ; Cui et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…BMSCs were seeded in 12-well plates at the density of 1×10 4 /well for 24 h. BMSCs were transduced with lentivirus expressing SIRT1 or control vector (lentivirus-SIRT1 and lentivirus-vector) (Thermo Fisher Scientific; Waltham, MA, USA) for 72 h. The transfection efficiency was detected by immunofluorescence staining, RT-qPCR and Western blotting.…”
Section: Lentiviral Transfectionmentioning
confidence: 99%
“…Recently, stem cell-based therapy which was regarded as a promising treatment for SUI (3). Bone marrow mesenchymal stem cells (BMSCs) are the first discovered and well-studied MSCs with outstanding differentiation capacity (4). Multiple studies have reported the efficacy of BMSCs in improving SUI in rats and humans (5,6).…”
Section: Introductionmentioning
confidence: 99%